(NaMERIKANSKAQ PESNQs (NISTORIQs - (Ng(B.(N{NEERSONs; (Na(B.(NmODINs (NREDAKTORs ((NmOSKWAs (NsOWETSKIJ kOMPOZITORs, 1977)
(NrABOTA POSWQ]ENA PESENNOMU ISKUSSTWU NARODOW sOEDINENNYH {TATOW aMERI(B-(NFOL_KLORNYM OBRACAM(B.s
Keywords: (NISTORIQs